Performance of bearing capacity for eco-friendly raft pile foundation system (ERP System) in soft soil - Abdul Rahman, Siti Saimah (2015)
In this study, the total bearing capacity estimation of Eco-Friendly Raft Pile Foundation System (ERP System) that act as a floating raft-pile system subjected to axial loading is presented. The proposed analysis is based on the conventional formulas and the secondary data from the results of foundation prototypes tested on site through Plate Bearing Test. In this study, analytical formulas to estimate the axial pile capacity and the group piles efficiency for piles in clay is reviewed. The calculation using the formulas is compared to the secondary data based on Plate Bearing Test results. Based on the calculation by validating the standard formula, it shows that the allowable bearing capacity is similar with allowable bearing capacity from the secondary data that obtained based on the field test. The axial capacity of the Eco-Friendly Raft Pile Foundation System (ERP System) floating in clays can be concluded higher than the original ground without ERP System. For practical application, the combination formula to estimate the total floating foundation load capacity for ERP System in soft clay is proposed.